SINERGITAS PEMBANGUNAN EKONOMI LOKAL DAN PARIWISATA MELALUI PERATURAN DAERAH TERINTEGRASI - Danu Suryani; Warizal Warizal (JURNAL ILMIAH LIVING LAW, 2019)
The high tourism visit is a potential that can be utilized to encourage local economic progress, this can be done on condition that the increase in tourism visits must be followed by an increase in the ability of the government and local communities to be able to synergize the tourism potential and the local economy because if not, an increase in tourism visits only adds benefits for tourism business activists who are not local residents so that local residents receive more negative impacts than positive impacts from increased tourism visits. This must be addressed, one of which is the synergy of the tourism potential management program with the local economic program in the local government.